Registry randomised trials: a methodological perspective - Christopher M Reid; Susannah Ahern; Ian Harris; Steven Y C Tong; Angela L Brennan; Dorota A Doherty; Carol Hodgson; Stephen McDonald; Jennifer Reilly; Jane Shrapnel; Charmaine S Tam; Leonie Wilcox; et al. (BMJ Open, 2023)
Registry randomised clinical trials (RRCTs) have the potential to provide pragmatic answers to important clinical questions. RRCTs can be embedded into large population-based registries or smaller single site registries to provide timely answers at a reduced cost compared with traditional randomised controlled trials. RRCTs can take a number of forms in addition to the traditional individual-level randomised trial, including parallel group trials, platform or adaptive trials, cluster randomised trials and cluster randomised stepped-wedge trials. From an implementation perspective, initially it is advantageous to embed RRCT into well-established registries as these have typically already overcome any issues with end point validation and adjudication. With advances in data linkage and data quality, RRCTs can play an important role in answering clinical questions in a pragmatic, cost-effective way.